2010
DOI: 10.5688/aj7407130
|View full text |Cite
|
Sign up to set email alerts
|

A Week-Long Diabetes Simulation for Pharmacy Students

Abstract: Objective. To assess students' attitudes and confidence about type 2 diabetes mellitus and diabetes self-management education before and after participation in Living With Diabetes Week simulation. Design. Third-year pharmacy students took part in diabetes lectures, interactive laboratory sessions, and a week-long simulation of life as a patient with diabetes in the Clinical Assessment course. Pre-/ postintervention survey instruments and experimental and control group comparisons were completed assessing atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…7,8 The incorporation of the DSME classes into the service-learning elective had a significant impact on student confidence in their DSME knowledge and skills. In addition, student performance in organizing and teaching the DSME classes was above average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The incorporation of the DSME classes into the service-learning elective had a significant impact on student confidence in their DSME knowledge and skills. In addition, student performance in organizing and teaching the DSME classes was above average.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] However, there are no published reports of group DSME classes facilitated by pharmacy students. A review of the literature revealed a single study that involved nursing student-facilitated DSME group classes using diabetes conversation maps.…”
mentioning
confidence: 99%
“…Studies in the literature involving undergraduate healthcare students engaged with virtual or real-life scenarios (using actors) in their study programs are predominantly grounded in simulation-based education 19,20 and in conjunction with interprofessional learning, [21][22][23] and patient safety units. 24,25 The current study offers new insights for teaching patient self-management through the use of indepth interviews connecting students with the experiences of real patients living with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In another simulation, pharmacy students engaged in a 6-week patient/provider interaction simulation. While results of diabetes simulations are positive with regards to improving empathy [6,7], self-efficacy [6], confidence in teaching diabetes self-management skills [4,5], and diabetes attitudes [5], none incorporated advanced critical thinking skills related to day-to-day challenges (unexpected hypo-or hyperglycemia, changes in glucose related to illness, stress, or exercise, etc.). Utilizing the expertise of real patients may benefit healthcare providers with regards to attaining complex skills and knowledge [8], improving communication [9], and supporting patient-centered learning [10].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a variety of approaches to simulation to provide education on diabetes management; however, few simulated experiences allow the learner to fully understand the day-to-day challenges of living with diabetes. Pharmacy students have participated in a 1-week simulation experience as if they had diabetes, checking glucose levels, taking saline injections, and logging diet and exercise [4,5]. In another simulation, pharmacy students engaged in a 6-week patient/provider interaction simulation.…”
Section: Introductionmentioning
confidence: 99%